Wedang Dokter - Sutanta, Sutanta; Hasbi, Habid Al; Ningrum, Andriani Noerlita (Jurnal Gema Ngabdi, 2025)
Public health can be improved through promotional and preventive efforts utilizing local herbal plants. Metuk Village has potential crops of ginger, turmeric, lemongrass, lime, and kepok banana waste that have not been optimally managed. The "Wedang Dokter" community service program aims to improve both the health and economic well-being of residents by utilizing herbal plants to produce health drinks. Implementation methods include outreach, production and packaging training, the application of appropriate technology, business management assistance, and digital marketing strategies. The activity results indicate an increase in the knowledge of Family Welfare (PKK) cadres about the benefits of herbal plants, their ability to produce and package wedang, and the development of a social media-based marketing strategy. The "Wedang Dokter" product was positively received by the community, as evidenced by the increased demand for the product during the program. This program supports the achievement of SDGs point 3 (Good Health and Well-Being) and Asta Cita through community empowerment and strengthening the local economy.